2022
DOI: 10.1177/00033197221129356
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Systemic Immune Inflammation Index for Predicting Saphenous Vein Graft Disease in Patients with Coronary Artery Bypass Grafting

Abstract: As inflammation plays a significant role in the development of coronary artery disease, we hypothesized that there may be a relation between the systemic immune inflammation index (SII) and saphenous vein graft disease (SVGD). The study population consisted of 716 consecutive patients who underwent elective coronary angiography (CAG) >1 year after bypass grafting. The patients were divided into 2 groups depending on the extent of SVG patency. SII value was significantly higher in the SVGD(+) group compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Furthermore, multiple genetic and sociological studies have found that family history is a significant risk factor for coronary artery disease [37][38][39][40]. Additionally, low-platelets being associated with coronary artery disease is associated with pathology such as thrombocytopenia [41][42][43]. In addition to the top four covariates within our model, we also wanted to explore if the machine-learning model was able to generate predictions for HDL-Cholesterol and Systolic Blood pressure, two major risk factors that have been widely studied within the cardiovascular literature.…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, multiple genetic and sociological studies have found that family history is a significant risk factor for coronary artery disease [37][38][39][40]. Additionally, low-platelets being associated with coronary artery disease is associated with pathology such as thrombocytopenia [41][42][43]. In addition to the top four covariates within our model, we also wanted to explore if the machine-learning model was able to generate predictions for HDL-Cholesterol and Systolic Blood pressure, two major risk factors that have been widely studied within the cardiovascular literature.…”
Section: Plos Onementioning
confidence: 99%
“…Systemic index >545 × 10 3 /mm 3 was proposed as postoperative atrial fibrillation risk factor (OR: 10.2; 95% CI: 5.1-20.2, p < 0.001; AUC: 0.91) in on pump surgical revascularization by Honue et al [123]. Dogdus et al [100] in their analysis presented SII value >935 × 10 3 /mL as a better saphenous vein graft predictor than NLR (OR: 3.27, 95% CI: 1.94-5.65, p < 0.001).…”
Section: Systemic Immune Inflammatory Index (Sii)mentioning
confidence: 99%
“…The authors 1 included 716 consecutive patients who underwent elective coronary angiography >1 year after coronary artery bypass grafting (CABG). They investigated the role of the systemic immune inflammation index (SII) in predicting the development of saphenous vein graft disease (SVGD) in these patients.…”
mentioning
confidence: 99%
“…6 A significant correlation was shown with the SYNTAX score in patients with coronary artery disease. 6 Could the high SII values in the study 1 be related to the high SYNTAX score? Moreover, atherosclerosis is a systemic disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation